2022
DOI: 10.1111/jre.13031
|View full text |Cite
|
Sign up to set email alerts
|

The role of endoplasmic reticulum stress in the pathophysiology of periodontal disease

Abstract: The endoplasmic reticulum (ER) is a principal organelle for folding, post‐translational modifications and transport of secretory, luminal, and membrane proteins. ER stress is a condition induced by the accumulation of unfolded or misfolded proteins owing to a variety of physiological and pathological phenomena. To overcome the deleterious effects of ER stress, unfolded protein response (UPR) is initiated to translocate and remove the misfolded and accumulated proteins. Plenty of evidence shows the correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 102 publications
(258 reference statements)
1
13
0
Order By: Relevance
“…Consistently, we obtained similar results in the KEGG pathway analysis, further probing that these DEGs are involved in protein processing in the ER. Moreover, our enrichment results are consistent with existing experimental studies, demonstrating the involvement of ER in the pathological pathway of periodontitis and proving the correlation between ERS and periodontitis [35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistently, we obtained similar results in the KEGG pathway analysis, further probing that these DEGs are involved in protein processing in the ER. Moreover, our enrichment results are consistent with existing experimental studies, demonstrating the involvement of ER in the pathological pathway of periodontitis and proving the correlation between ERS and periodontitis [35].…”
Section: Discussionsupporting
confidence: 91%
“…ERAD can protect cells from the adverse effects of ERS, but excessive ERAD can be harmful 10 Disease Markers by disrupting cellular homeostasis and inducing apoptosis via UPR [42]. Moreover, when ERS induces excessive tissue apoptosis, destruction of periodontal soft tissues can occur [35]. A recent study has shown that proper expression levels of ERLEC1 are critical in osteogenic differentiation, and the occurrence of abnormal jaw development could be associated with pathogenic variants of ERLEC1 [43].…”
Section: Discussionmentioning
confidence: 99%
“…This indicated an inhibitory effect of miR-1260b on ER stress. Although the association between ER stress and periodontal disease has been well accepted ( Jiang et al, 2022 ), the direct effect of ER stress on osteoclastogenesis remains unclear. Yamada et al (2015) reported that the ER stress inducer, tunicamycin, did not induce osteoclast differentiation without RANKL.…”
Section: Discussionmentioning
confidence: 99%
“…Its pathology is characterized by inflammation of the periodontium and subsequent destruction of the tooth-supporting alveolar bone, which is a major cause of tooth loss in adults ( Kajiya and Kurihara, 2021 ). Recently, studies have focused on the influence of endoplasmic reticulum (ER) stress on periodontitis ( Jiang et al, 2022 ). ER is the principal organelle that plays an essential role in the folding and structural maturation of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…A surge of evidence has emerged linking the pathology of various diseases to ER stress and UPR [ 8 , 9 ]. In recent years, an increasing number of studies have concentrated on the involvement of ER stress in the pathophysiology of chronic obstructive pulmonary disease (COPD).…”
Section: Introductionmentioning
confidence: 99%